Perancangan Interior Pusat Penampungan dan Pelatihan Gelandangan dan Pengemis Surabaya - Ane, Trifena Magdalena (Intra, 2015)
The phenomenon of the increasing number of homeless and beggars in Surabaya is a social welfare problem caused by the infrastructure that grows unevenly, which cause great migration from suburban to urban area, where not all people has enough ability or education. The âHarapan Baruâ social parlors is designed as a shelter and training ground with a certain time span so they can learn and hopefully be equipped with something that can be used to get a good living. The concept used is âAmeliorate Gemstoneâ which means something will be valuable after being sharpened and going through several processes. That concept is applied through variety of rooms that use durable materials and able to answer all the resident needs, it also includes the nature elements like vertical garden, lighting system, and natural ventilation. This aims for energy and cost saving, as well as a learning for the occupant in processing scraps.